Strategi Adaptasi Sistem Pengetahuan Adat Komunitas Kampung Kuta dalam Menghadapi Tekanan Globalisasi: Studi Kritis Terhadap Ketahanan Budaya dan Konservasi Alam - Nurholis, Egi; Sudarto, Sudarto; Budiman, Agus; Ramdani, Dadan (Jurnal Artefak, 2025)
This study examines the impact of globalization on the indigenous knowledge system of the Kuta Village community in Ciamis and the adaptation strategies they employ to maintain cultural resilience and environmental sustainability. Using a qualitative approach through in-depth interviews, participatory observation, and document analysis, the research finds that the community integrates traditional rules (pamali), sacred forest preservation rituals, cultural education, and selective use of environmentally friendly technologies. Traditional institutions act as key mediators between tradition and modernization, ensuring sustainable use of natural resources. These strategies not only preserve cultural identity but also strengthen the ecological functions of the customary territory. The findings highlight that local wisdom-based adaptation can effectively respond to globalization pressures without sacrificing core values. The study recommends formal recognition and policy support for indigenous knowledge systems as vital social capital for sustainable development.